Dynamics of Social Innovation in the Public Sector of Khyber Pakhtunkhwa - Wasai, Sundus; Awan, Hassan; Nouman, Muhammad (The Lighthouse Journal of Social Sciences, 2024)
This research generates an in-depth understanding of social innovation process by conducting empirical inquiry in the public sector of Khyber Pakhtunkhwa, Pakistan. Taking influence from case study strategy, three social innovation projects have been selected as cases. Research findings reveal that social innovations take place in the form of new services addressing social needs and creating public value. The stages of social innovation process initially occur in a linear and later in a non-linear sequence, with overlapping spaces. However, these social innovations do not fully go through all stages of the process specifically sustainability (except in one case) and systemic change (in all the cases). Moreover, important factors that influence the process of social innovations have been identified as well as recommendations and contributions are provided.